AL-KINDĪ’S METAPHYSICS: THE INTEGRATION OF GREEK PHILOSOPHY IN ISLAMIC PHILOSOPHY - Armayanto, Harda; Suntoro, Adib Fattah; Faruqi, Achmad Reza Hutama Al; Ulfa, Maria (Sekolah Tinggi Agama Islam Sadra, 2025)
This study aims to rectify the reductionist assumption that Islamic philosophy is merely a replication of ancient Greek thought. Specifically, it analyzes how al-Kindī, as one of the pioneers of philosophy within the Islamic tradition, systematically integrated elements of Greek philosophy—particularly Neoplatonism and Aristotelianism—into the conceptual framework of Islamic thought, with a focus on metaphysical aspects of divinity. The central theological themes examined include arguments concerning the existence of God, the essence and characteristics of God, and the concept of the creation of the universe. Using a descriptive-qualitative approach to al-Kindī’s primary texts, particularly Fī al-Falsafah al-Ūlā, this study reveals that al-Kindī did not merely adopt Greek philosophical ideas passively. Rather, he actively selected, reinterpreted, and reformulated these ideas to align with the foundational principles of Islamic teachings. The findings indicate that al-Kindī functioned as more than a translator or conduit of intellectual traditions; he emerged as an innovator who successfully synthesized philosophical reasoning with religious revelation. Another significant finding is al-Kindī’s critical stance toward Greek metaphysical concepts—for instance, his rejection of the notion of creatio ex materia (creation from pre-existing matter) in favor of creatio ex nihilo (creation from nothing), which is more consistent with Islamic theology. This contribution marks the formation of an original and contextual Islamic metaphysical system and paved the way for the more systematic development of Islamic philosophy in subsequent periods. Therefore, this study underscores the importance of repositioning al-Kindī as a central figure in the intellectual history of Islam, one who effectively bridged two major intellectual legacies: Greek philosophy and Islamic thought.